1995
DOI: 10.1111/j.1365-2885.1995.tb00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of trimethoprim/sulphachlorpyridazine in horses after oral, nasogastric and intravenous administration

Abstract: In the present study, the pharmacokinetic parameters of a trimethoprim/sulphachlorpyridazine preparation following intravenous administration, administration by nasogastric tube and administration with concentrate were determined in the horse. Eight adult horses were dosed at 1 week intervals in a sequentially designed study at a dose of 5 mg/kg trimethoprim (TMP) and 25 mg/kg sulphachlorpyridazine (SCP) on all occasions. Plasma concentrations of both drugs were measured serially for 48 h. Pharmacokinetic para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…The great variation in T max between individual ponies found in the present study (range 1–9 h) has also been found by others (van Duijkeren et al ., 1995; Gustafsson et al ., 1999). The bi‐phasic absorption seen in two ponies has been described earlier for a TMP/sulfachlorpyridazine combination in horses fed concentrates (van Duijkeren et al ., 1995) and for phenylbutazone in ponies fed hay (Maitho et al ., 1986). When horses were fasted 12 h before TMPS administration no double peaks were obtained (van Duijkeren et al ., 1994b).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The great variation in T max between individual ponies found in the present study (range 1–9 h) has also been found by others (van Duijkeren et al ., 1995; Gustafsson et al ., 1999). The bi‐phasic absorption seen in two ponies has been described earlier for a TMP/sulfachlorpyridazine combination in horses fed concentrates (van Duijkeren et al ., 1995) and for phenylbutazone in ponies fed hay (Maitho et al ., 1986). When horses were fasted 12 h before TMPS administration no double peaks were obtained (van Duijkeren et al ., 1994b).…”
Section: Discussionsupporting
confidence: 92%
“…Trimethoprim–sulfonamide (TMPS) combinations are used extensively in equine practice because of their broad spectrum of activity against many Gram‐positive and Gram‐negative bacteria and their clinical efficacy (van Duijkeren et al ., 1994a). Moreover, TMPS combinations have a relatively high bioavailability following oral administration (van Duijkeren et al ., 1994b; van Duijkeren et al ., 1995) with only minor effects on the equine intestinal flora (Ensink et al ., 1996b; Gustafsson et al ., 1999). Generally, effective antimicrobial therapy should produce and maintain effective concentrations of the drug at the site of infection for a sufficient period of time to kill or inhibit bacteria without toxic effects to the host (Prescott & Baggot, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the DiXa drug was given carefully by mouth and not by nasogastric tube. It should be considered that this type of drug administration may lead to an unknown amount of drug loss at the moment of oral administration . However, the authors consider this possibility unlikely given that great care was used during oral administration of the DiXa drug and at no time did horses drop the mixture of drug with honey.…”
Section: Discussionmentioning
confidence: 99%
“…SDZ/TMP ratios in equine plasma have been studied after intravenous and oral administration (Van Duijkeren et al. , 1994a; Van Duijkeren et al. , 1995b), and the 20:1 ratio in plasma was approached up to 6 h after intravenous administration and approximately up to 9 h after repeated oral administrations.…”
Section: Introductionmentioning
confidence: 99%